Respuesta :
Answer:
Parallel
Step-by-step explanation:
-y₁ + y₂\-x₁ + x₂ = m
[tex] \frac{2 + 7}{ -5 + 8} = \frac{9}{3} = 3[/tex]
[tex] \frac{0 + 6}{6 - 4} = \frac{6}{2} = 3[/tex]
Both rate of changes [slopes] result in three, therefore both lines are parallel.
I am joyous to assist you anytime.
Lines can be parallel, perpendicular or neither
Both lines are neither perpendicular nor parallel
The first line passes through (-6,0) and (-4,6)
The slope (m1) of the first line is:
[tex]m_1 = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
So, we have:
[tex]m_1 = \frac{6-0}{-4--6}[/tex]
[tex]m_1 = \frac{6}{2}[/tex]
[tex]m_1 = 3[/tex]
The second line passes through (5,-2) and (8,7)
The slope (m2) of the second line is:
[tex]m_2 = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
So, we have:
[tex]m_2 = \frac{7--2}{8-5}[/tex]
[tex]m_2 = \frac{5}{3}[/tex]
- If [tex]m_1 = m_2[/tex], then the lines are parallel
- If [tex]m_1 = -\frac{1}m_2[/tex], then the lines are perpendicular
None of the above conditions is true.
Hence, the lines are neither perpendicular nor parallel
Read more about perpendicular and parallel lines at:
https://brainly.com/question/12731518